Peran strategis mahasiswa KKN dalam edukasi lingkungan menggerakkan green campus - Muh. Syahril Mubaraq A. Taufan; Aldi Ashary; Muhammad Syukur Kahar; Nurul Pratiwi; Nurul Putri Amalia; Taufik Hidayat; Rini Anggriani; Andi Sulfanita; Suherman (Jurnal Dedikasi Masyarakat, 2022)
The 2021 Community Service Program (KKN) Group 4 of Universitas Muhammadiyah Parepare adopted a participatory approach to strengthen the green campus culture in the Campus II environment. The program began by mapping the problems of organic and inorganic waste management, followed by training in composting and recycling plastic waste into useful products, education on the cleanliness of public facilities, as well as fun walks and blood donation activities, all aimed at promoting social sustainability. Field documentation and periodic reflections were used for evaluation, while descriptive analysis focused on program achievements, the level of academic community participation, and sustainability potential. The results showed active involvement of up to 75% in composting (∼12 kg of organic waste/week), an increase in satisfaction with public facilities by 60%, and the formation of an environmentally friendly lifestyle through messages about reducing plastic waste. The experiential learning and service learning approaches have proven effective in instilling sustainability values, while the participatory model encourages collaboration across campus elements. Recommendations include the establishment of an environmental management unit and the integration of environmentally friendly activities into extracurricular and applied curricula.